2017
DOI: 10.31258/jnat.17.1.33-41
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Partikel Arang Sekam Padi Dan Waktu Refluks terhadap Kadar Abudan Daya Serap Karbon Sekam Padi

Abstract: The highest content in rice husk is ash with its main component of silica. Silica in ash causes the low adsorption capacity. Activated carbon from rice husk can be obtained by lowering the ash content. The aim of this study is determine the effect of particle size of charcoal and reflux time the ash content using a solution of potassium carbonate. The activation of rice husk char was carried out by using reflux methods with a potassium carbonate solution. The resulted carbon was washed using hydrochloric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have shown the relationship between temperature and time on the yield of hull charcoal produced (Karam et al, 2022). Siahaan et al (2013) and Solihudin (2016) have reported that the pyrolysis temperature and incubation time have an impact on the carbon content of hull charcoal. Seeing this effect, it is necessary to further investigate the impact of pyrolysis temperature and time on other physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the relationship between temperature and time on the yield of hull charcoal produced (Karam et al, 2022). Siahaan et al (2013) and Solihudin (2016) have reported that the pyrolysis temperature and incubation time have an impact on the carbon content of hull charcoal. Seeing this effect, it is necessary to further investigate the impact of pyrolysis temperature and time on other physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%